Race/Ethnicity and Informal Caregiver Burden After Traumatic Brain Injury: A Scoping Study (Mary Ann Liebert, 2020)
Background: Informal caregivers for persons with traumatic brain injury (TBI) face a range of unique issues, and racial/ethnic group differences in caregiver challenges are poorly understood. We undertook a scoping study of peer-reviewed literature to assess the quantity and quality of available research describing differences by race/ethnicity in informal caregiving roles and burden. Methods: Using Arksey and O'Malley's framework and guided by the Preferred Reporting Items of Systematic Reviews and Meta-analyses Extension for Scoping Reviews, we conducted electronic searches of PubMed, CINAHL, PsycARTICLES, PsycINFO, Social Work Abstracts, Embase, and Scopus to identify peer-reviewed studies that examined TBI informal caregiver burden and reported on the influences of race or ethnicity. Results: Among 4523 unique publications identified and screened, 11 studies included sufficient race/ethnicity data and were included in the analysis. Of these, six studies described civilian populations and five described military Veterans Affairs (VA). Included studies revealed that nonwhite caregivers and white caregivers use different approaches and coping strategies in their caregiving role. Some studies found differences in caregiver burden by race or ethnicity, others did not. Most were limited by a small sample size and overdependence on assessment tools not validated for the purposes or populations for which they were used. This was particularly true for race/ethnicity as a factor in TBI caregiver burden in VA groups, where essential characteristics moderate the association of race/ethnicity with socioeconomic factors. Conclusions: This scoping study highlights the paucity of information on race/ethnicity as a factor in TBI caregiver burden and roles, and suggests that innovative and alternative approaches to research are needed to explore needed changes in practice.